2017
DOI: 10.1016/j.ica.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and anti-Mycobacterium tuberculosis agents based on cationic ruthenium complexes with amino acids

Abstract: Six new complexes of Ru(II)/phenanthroline/1,4-bis(diphenylphosphino)butane containing amino acids (Glycine, L-Alanine, L-Valine, L-Tyrosine, L-Methionine or L-Tryptophan) were synthesized and characterized by IR, 31 P{ 1 H}, 13 C and 1 H NMR spectroscopies and cyclic voltammetry experiments. These data suggest the presence of diastereoisomers, except for the complex with glycine, amino acid that does not exhibit chiral carbon. The compounds are active against the MDA-MB-231 tumor cells and against Mycobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Our research group found that phosphinic ligands and other ligands with properties of biological interest, such as diimines, nitric oxide, carbon monoxide (CO) and amino acids coordinated to the ruthenium metal center, exhibited relevant characteristics in different biological assays (Barbosa et al, ; Lima et al, ; Mondelli et al, ; Oliveira et al, ; Porto et al, ; Santos et al, ). We have recently published a study demonstrating the antitumor activity of the ruthenium(II) compound, ct‐ [RuCl(CO)(dppb)(bipy)]PF 6 (where dppb = 1,4‐bis(diphenylphosphino)butane and bipy = 2,2′‐bipyridine), in in vitro and in vivo assays, as well as its interactions with ctDNA and bovine serum albumin.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group found that phosphinic ligands and other ligands with properties of biological interest, such as diimines, nitric oxide, carbon monoxide (CO) and amino acids coordinated to the ruthenium metal center, exhibited relevant characteristics in different biological assays (Barbosa et al, ; Lima et al, ; Mondelli et al, ; Oliveira et al, ; Porto et al, ; Santos et al, ). We have recently published a study demonstrating the antitumor activity of the ruthenium(II) compound, ct‐ [RuCl(CO)(dppb)(bipy)]PF 6 (where dppb = 1,4‐bis(diphenylphosphino)butane and bipy = 2,2′‐bipyridine), in in vitro and in vivo assays, as well as its interactions with ctDNA and bovine serum albumin.…”
Section: Introductionmentioning
confidence: 99%
“…These conjugates demonstrated a better activity against breast cancer cells compared to the reference drug cisplatin and the non-amino acid conjugate ruthenium(II) complex, with an IC 50 ranging from 3.04 to 7.44 µM. Among all of the developed compounds, complex 5c bearing the Tyr residue exhibited the best activity [66].…”
Section: Natural Product-conjugated Metal Complex Cancer Therapiesmentioning
confidence: 99%
“…The binding affinity towards targeted active sites is of great importance for cancer therapy development based on the similar hydrophilic–lipophilic ability of the treatment molecule and the corresponding targeting receptors [66]. Ruiz and coworkers recently developed a lipophilic levonorgestrel-conjugated ruthenium(II) complex 7a (Figure 8) against breast cancer [67].…”
Section: Natural Product-conjugated Metal Complex Cancer Therapiesmentioning
confidence: 99%
“…3 Recently, a great number of ruthenium complexes containing different ligands, have been tested as antitumor agents against different kinds of tumor cell lines, showing to be very active. [4][5][6][7][8][9] Thus, picolinate containing complex [Ru(η 6 -p-cymene)Cl(picolinate)] is active against HeLa (drug concentration at which 50% of the cells are viable relative to the control (IC 50 ) = 82.0 μM) and human melanoma cells (FemX, IC 50 = 36.2 μM). 10 The possible reason for this behavior is that the [Ru(η 6 -p-cymene) Cl(picolinate)] accumulates in the deoxyribonucleic acid (DNA) molecule, since it has high affinity for DNA-binding.…”
Section: Introductionmentioning
confidence: 99%